Pemanfaatan Media Digital Sebagai Strategi Aktif dalam Pembelajaran PAI Era Society 5.0 - Yana Puspita Sari; Rahmat Hidayat; Gusmaneli Gusmaneli (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The utilization of digital media in Islamic Religious Education (IRE) learning in the Society 5.0 era has become one of the crucial strategies to address the challenges posed by technological advancements and social dynamics. This study aims to examine the role of digital media in enhancing the quality of IRE learning, as well as its impact on the transformation of teachers' roles and the development of students' religious character. The research method employed is a literature review, analyzing various sources related to the use of digital media in religious education, active learning strategies based on technology, and their effects on learning outcomes. The findings of the study reveal that digital media can increase students' interest and motivation in learning, enrich the learning experience, and foster a more critical and creative student character. However, challenges such as the digital divide and the low digital competency of teachers need to be addressed to maximize the potential of digital media in IRE learning. This study contributes to the development of Islamic education that is adaptive to the changing times and technologies.